Biznesa inkubatoru darbības un perspektīvu analīze Latvijā. - Linkuma, Ilze (Latvijas Universitāte, 2013)
Bakalaura darbs „Biznesa inkubatoru darbības un perspektīvu analīze Latvijā”. Pētījuma hipotēze „Biznesa inkubatoru darbība ir Latvijas ekonomikai nozīmīga” pētījuma gaitā ir apstiprināta. Darba mērķis: izpētīt biznesa inkubatoru darbību un dot priekslikumus to atīstībai. Darba uzdevumi: raksturot biznesa inkubatoru darbības teorētiskos aspektus; raksturot biznesa inkubatoru darbību; apkopot galvenos secinājumus un priekšlikumus. Pētījums praktiski izmantojams biznesa inkubatoru attīstībā. Bakalaura darba apjoms 66 lapaspuses, tajā ietverti 5 attēli, 4 tabulas un 1 pielikums. Atslēgvārdi: inovācijas, biznesa inkubatori, atbalsts uzņēmējdarbībai.

Bachelor paper „Analysis of business incubator activities and future possibilities in Latvia". The hypothesis of the study „The activities of the business incubators in Latvia are significant for the economy of Latvia” has been proved during the study. The objective of the paper: to study the activities of business incubators in the world and Latvia, the significance of the activities, problems and development possibilities. The tasks of the paper: to describe the theoretical aspects of the business incubator activity; to describe the activity of an business incubator; to summarize the main conclusions and proposals. The study has a practical meaning and can be applied for the purposes of business incubator development. The research contains 66 pages, 5 images, 4 tables and 1 appendice. The keywords: innovations, business incubators, entrepreneurship support.
Analysis of business incubator activities and future possibilities in Latvia.
Keywords: Vadībzinātne